2021
DOI: 10.1186/s12880-021-00610-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative ultrasound radiomics analysis for expression of multiple molecular biomarkers in mass type of breast ductal carcinoma in situ

Abstract: Background The molecular biomarkers of breast ductal carcinoma in situ (DCIS) have important guiding significance for individualized precision treatment. This study was intended to explore the significance of radiomics based on ultrasound images to predict the expression of molecular biomarkers of mass type of DCIS. Methods 116 patients with mass type of DCIS were included in this retrospective study. The radiomics features were extracted based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…8 Radiomics 9 is an artificial intelligence method used to extract, select, and classify many image features in a high-throughput manner to construct an appropriate model for clinical diagnosis, prognosis, histological subtype prediction, and efficacy evaluation of diseases. [10][11][12][13][14] Radiomics can be coupled with various imaging examinations, such as mammography, ultrasonography, computed tomography, and magnetic resonance imaging. 15 Recently, a radiomics study based on breast ultrasonography has shown good performance classifying breast benign and malignant lesions.…”
mentioning
confidence: 99%
“…8 Radiomics 9 is an artificial intelligence method used to extract, select, and classify many image features in a high-throughput manner to construct an appropriate model for clinical diagnosis, prognosis, histological subtype prediction, and efficacy evaluation of diseases. [10][11][12][13][14] Radiomics can be coupled with various imaging examinations, such as mammography, ultrasonography, computed tomography, and magnetic resonance imaging. 15 Recently, a radiomics study based on breast ultrasonography has shown good performance classifying breast benign and malignant lesions.…”
mentioning
confidence: 99%
“…developed a machine-learning model for predicting VEGF status in patients with diffuse gliomas, and the AUC was 74.1% in the training group and 70.2% in the validation group ( 63 ). Other studies have also applied radiomics based on different imaging techniques to predict the expression status of p53 in epithelial ovarian cancer ( 64 ), endometrial carcinoma ( 65 ), esophageal squamous cell carcinoma ( 66 ), and breast ductal carcinoma ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 11 ] conducted a study using a radiomics analysis on grayscale ultrasound images that managed to predict the HER2 and hormone receptor status of DCIS with good accuracy. In our study, the multivariate analysis showed that no parameters were independent predictors for the PR+ status.…”
Section: Discussionmentioning
confidence: 99%
“…Breast radiomics studies are mostly applied to the diagnosis of breast cancer, the prediction of the molecular classification, lymph nodes metastasis and molecular markers of invasiveness [ 9 , 10 , 11 , 12 ]. Luo et al [ 13 ] found in their study that radiomics had better performance in distinguishing breast lesions than BI-RADS, and according to Wang et al [ 14 ], radiomics was superior in differentiating small benign and malignant breast lesions.…”
Section: Introductionmentioning
confidence: 99%